Leverage, Firm Size, and Environmental Performance as Determinants of Carbon Emission Disclosure: An Educational Perspective of Energy and Industrial Sector Firms Listed on the Indonesia Stock Exchange - Alamanda, Kartika Inayah; Azis, Mohammad Taufik; Djajuli, Mohamad (Journal Corner of Education, Linguistics, and Literature, 2025)
This study examined the influence of leverage, firm size, and environmental performance on carbon emission disclosure among energy and industrial sector firms listed on the Indonesia Stock Exchange during the 2021–2024 period. The analysis reveals that leverage and firm size do not have a significant impact on disclosure, indicating that debt levels and organizational scale are not central determinants of environmental transparency. Conversely, environmental performance—measure through the PROPER rating—exerts a positive and significant influence, suggesting that firms with stronger environmental achievements demonstrate greater commitment to disclosing carbon-related information. Framed within an educational perspective, these findings highlight the critical role of environmental accountability in shaping organizational learning, stakeholder awareness, and the dissemination of sustainability values. The results contribute to both academic and practical knowledge by emphasizing that environmental responsibility, rather than financial or structural attributes, is a more effective driver of carbon disclosure. This reinforces the importance of integrating sustainability and disclosure practices into corporate training, higher education curricula, and professional development initiatives to cultivate long-term awareness and accountability.